Non-specific effects of different sham acupuncture methods and their impact on true acupuncture effectiveness in migraine: a protocol for systematic review and network meta-analysis - Fan Jiang; Haifeng Zhang; Lun Li; Qinhong Zhang; Meng Lin; Yongjian Liu; Yong Fu; Jiahui Yang; Qilin Liu; Meiyi Zhu; Xiumei Yan (BMJ Open)
Introduction Migraine, a major headache disorder of high prevalence, affects approximately one billion individuals globally and imposes a substantial socioeconomic burden. Acupuncture, as a modality of complementary and alternative medicine, is increasingly used by patients for migraine management. Nevertheless, the effectiveness of acupuncture in randomised controlled trials (RCTs) for this condition remains a subject of debate. The varying non-specific effects of different sham acupuncture (SA) techniques complicate the accurate assessment of true therapeutic effectiveness of acupuncture. This protocol details a systematic review and network meta-analysis (NMA) aimed at comprehensively evaluating both the effectiveness of acupuncture compared with various sham controls and the differential non-specific effects of different SA methods in migraine. Our aims involve: (1) evaluating the effectiveness of acupuncture relative to SA controls in migraine treatment; (2) comparing the effect sizes across different SA methods and (3) identifying potential factors that influence the outcomes associated with various sham interventions.Methods and analysis We will undertake a thorough investigation using multiple databases, including Wanfang Data, Cochrane Library, Web of Science, Embase, ClinicalTrials.gov, PubMed, Chongqing VIP Database, SinoMed, Cochrane Central Register of Controlled Trials, Chinese Clinical Trial Register, International Traditional Medicine Clinical Trial Registry and China National Knowledge Infrastructure, spanning from their initial records up to 12 November 2024. The inclusion criteria are RCTs that compare acupuncture with SA controls for migraine treatment. Studies with waiting-list or no-treatment controls will be included only if they also contain an SA arm. Studies focusing exclusively on chronic migraine patients (≥15 headache days per month) will be excluded. Two independent reviewers will perform study selection, data extraction using a standardised prepiloted form and risk of bias assessment. The primary outcome will be the standardised mean difference (SMD) in migraine frequency measures, allowing for the inclusion of various frequency metrics (eg, migraine attacks, migraine days, headache days). Secondary outcomes will include response rate (≥50% reduction in frequency), days with acute medication use, the number of migraine days per month, pain intensity (measured using tools such as the Visual Analogue Scale or Numeric Rating Scale), and scores from migraine-specific questionnaires, among others. The Cochrane Risk of Bias tool 2 (RoB 2) will be employed for bias assessment, along with the Confidence in Network Meta-Analysis online tool and the Grading of Recommendations Assessment, Development and Evaluation system. A frequentist NMA will be executed using Stata (V.18.0). The network structure will comprise: acupuncture as a single node (or multiple nodes if heterogeneity warrants), different SA methods as separate nodes, and waiting-list/no-treatment as a single node. In terms of continuous outcomes, the synthesis will be conducted using the SMD with a 95% CI for estimating effects. Heterogeneity, network inconsistency and potential publication bias will be scrutinised. As needed, meta-regression, subgroup analyses and sensitivity analyses will be executed.Ethics and dissemination Since this research is based on data from published sources, it does not necessitate formal ethical clearance. The results will be shared via articles in scholarly journals and during presentations at academic symposiums.PROSPERO registration number CRD42024620550.